The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.15436/2376-0494.15.032
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological changes following liposuction of large volumes of fat in overweight and obese women

Abstract: Background Liposuction can remove a substantial amount of body fat. We investigated the effects of liposuction of large volumes of fat on anthropometrics, body composition (BIA), metabolic hormones, and psychological measures in overweight/obese women. To our knowledge, this is the first study to examine both physiological and psychological changes following liposuction of large volumes of fat in humans. Method Nine premenopausal healthy overweight/obese women (age = 35.9 ± 7.1 SD, weight = 84.4 kg ± 13.6, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…And some studies have found that central obesity is positively associated with cardiovascular disease (CVD) risk and some other diseases (26,27). Other studies showed that waist circumference decreased signi cantly after liposuction (F 3,24 = 44.5, p < 0.001; post hoc, all p's < 0.03) (28)(29)(30). However, to our knowledge, very few studies have discussed the connection between WC and liposuction volume and provided an equation for lipoaspirate estimation.…”
Section: Discussionmentioning
confidence: 91%
“…And some studies have found that central obesity is positively associated with cardiovascular disease (CVD) risk and some other diseases (26,27). Other studies showed that waist circumference decreased signi cantly after liposuction (F 3,24 = 44.5, p < 0.001; post hoc, all p's < 0.03) (28)(29)(30). However, to our knowledge, very few studies have discussed the connection between WC and liposuction volume and provided an equation for lipoaspirate estimation.…”
Section: Discussionmentioning
confidence: 91%
“…Saleh et al, [7] in their study showed that significant effect in buttock and thigh measurements preoperatively and 4 months after large volume liposuction. Geliebter et al, [13], found that abdominal circumference decreased overtime, in periods from October 2015 to May 2017 with total of 83 patients.…”
Section: Discussionmentioning
confidence: 98%
“…Geliebter et al, [13], demonstrated that body composition analysis at 10 weeks after liposuction caused a (9.4±1.8) kgreduction in body fat (16±2%) of total fat mass. While the visceral adipose tissuedid not change.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these results, a study in New York, United States using the same BSQ tool reported significant improvements in body shape concerns following liposuction. [30] A main objective of cosmetic interventions in general, and liposuction in particular, is to improve patients' selfesteem. In the present study, the scores of self-esteem were low in all its three domains of appearance, academic performance, and social evaluation.…”
Section: Discussionmentioning
confidence: 99%